Application of Design Innovation and Digital Technology in the Upcycling-based Clam Shell Craft Industry - Faza Wahmuda; Andy Rachman; Rony Prabowo (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Mekar Sari, a craft industry based on shell waste in Situbondo, East Java, encounters challenges related to limited production technology and monotonous product designs. These factors impede productivity and competitiveness in both local and international markets. This community service program aims to address these challenges through three primary activities: (1) assisting in the utilisation of a tuner engraving drill, a bench sander, and a CNC laser engraving machine to enhance production efficiency and quality; (2) facilitating the diversification of raw materials and the development of more innovative product designs, including the exploration of wood waste as an additional material; (3) offering training in the creation of more functional and aesthetically pleasing product designs; and (4) conducting digital marketing training to broaden market reach. The outcomes of these activities indicate a significant improvement in both the productivity and quality of Mekar Sari's craft products, characterised by more creative and appealing design variations. Furthermore, the diversification of raw materials has successfully expanded the product range, creating new opportunities for market expansion in domestic and international contexts.